(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This longitudinal study examines the impact of vocational development programs on the career trajectories of polytechnic students, specifically in entrepreneurial skill development. The study involves a sample of polytechnic students who participated in a vocational development program to enhance their entrepreneurial skills. Data was collected through surveys and interviews, both during and after the program. The results suggest that the vocational development program had a positive impact on the students’ entrepreneurial skills, as well as their career trajectories. The program helped the students develop essential skills such as communication, problem-solving, and innovation, which were found to be critical factors in their success as entrepreneurs. Additionally, the study found that the program had a long-term impact, with the skills and knowledge gained by the students continuing to benefit them even after they had completed their education. The study highlights the importance of vocational development programs in helping students develop the skills and knowledge needed to succeed in today’s rapidly changing job market, particularly in fields such as entrepreneurship.